Introducing dynamic stimulation aberrometry: binocular objective accommodation versus subjective measures - Hammer, Maximilian; Heggemann, Yvonne; Auffarth, Gerd U. (Ophthalmology science, 2023)
Purpose - The objective measurement of binocular accommodation remains a challenge. The dynamic stimulation aberrometry (DSA) system uses wavefront measurements to dynamically assess accommodation. In this study, we sought to introduce this method in a large number of patients of varying age and compared it with the subjective push-up method as well as the historical results of Duane. - Design - This study is an evaluation of diagnostic technology. - Subjects - Ninety-one patients aged 20 to 67 years (70 healthy, phakic eyes and 21 myopic eyes after phakic intraocular lens implantation) were enrolled at a tertiary eye hospital. - Methods - All patients underwent DSA measurements; the accommodative amplitude of 13 patients chosen at random was additionally examined using the subjective push-up method introduced by Duane. DSA measurements were also compared with Duane’s historical results. - Main Outcome Measures - Accommodative amplitude, dynamic parameters of accommodation, and near pupil motility. - Results - Dynamic stimulation aberrometry allowed objective measurement of binocular accommodation, which decreased with age (e.g., 30-39 years vs. > 50 years; 3.8 ± 0.9 diopters [D] and 0.1 ± 0.4 D, respectively). Dynamic parameters, such as time delay of the commencement of accommodation after near target presentation, increased with age (0.26 ± 0.14 seconds for 20-30 years vs. 0.43 ± 0.15 seconds for 40-50 years, P = 0.0002). The objective accommodative amplitude was significantly smaller than Duane’s historic results (P = 0.001) as well as the subjective push-up method. Dynamic stimulation aberrometry records pupil motility dynamically in parallel to wavefront measurements. Maximum pupil motility during accommodation significantly decreased with age (P = 0.0002). Maximum pupillary speed did not correlate significantly with age. - Conclusions - Dynamic stimulation aberrometry allows objective, dynamic, binocular measurement of accommodation and pupil motility with high time resolution in subjects with accommodative amplitudes up to 7 D. This article introduces the method in a large study population and may serve as a control for further studies. - Financial Disclosure(s) - Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.